Contact Hypersensitivity to Lavender Oil in Hungary: A Multicentre Survey 2013-2014 - Györgyi Pónyai; Anita Altmayer; Beáta Fábos; Beatrix Irinyi; Gabriella Nagy; Mária Dinnyés; Valéria Kohánka; Ilona Németh; Erzsébet Temesvári (Journal of Dermatologic Research And Therapy, 2015)
Background: Lavender has been used for centuries, but its exposure has become part of the everyday life in our days. It is used in the alternative medicine, and as a flavouring component in soaps, cosmetics and in food products (chocolate, ice-cream, spices). The increasing number of exposures resulted the appearance of hypersensitivity- reactions. Objectives: A survey on the prevalence of lavender hypersensitivity was conducted by the Contact Dermatitis Work-Group of the Hungarian Dermatological Society in a multicentre, prospective study. Patients and Methods: 1509 consecutivedermatological patients of 7 dermatological centres were involved in this study. Results were based on the analyses of age distribution and characteristic clinical signs of the patients, on symptoms-localization, and on relevance of positive skin lavender oil test results as well as other associated contact hypersensitivities. Results: We detected 8 patients with lavender hypersensitivity (0.53%). Typical localisations of skin symptoms were face, eyelids and hands. Associated hypersensitivity to fragrance and balsam components were not detected. Conclusion: The lavender hypersensitivity of our patients couldn’t be detected by fragrance screening allergens.The use of lavender oil in cosmetics and foods is very popular. The different types of contacts may result further increase of the sensitivity rate worldwide.
Keywords: lavender oil